2021
DOI: 10.1093/treephys/tpab118
|View full text |Cite
|
Sign up to set email alerts
|

Responses of fine root exudation, respiration and morphology in three early successional tree species to increased air humidity and different soil nitrogen sources

Abstract: Global climate change scenarios predict an increase in air temperature, precipitation, and air humidity for northern latitudes. Elevated air humidity may significantly reduce the water flux through forest canopies and affect interactions between water and nutrient uptake. However, we have limited understanding of how altered transpiration would affect root respiration and carbon (C) exudation as fine root morphology acclimates to different water flux. We investigated the effects of elevated air relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In our study, the proportions of net-C assimilation allocated to root exudation were only 0.6 AE 0.1% and 1.8 AE 0.6% in control and drought plots, respectively, which were below the 3-30% previously reported at other study sites for multiple species (Kuzyakov & Domanski, 2000;Jones et al, 2009;Finzi et al, 2015;Abramoff & Finzi, 2016;Gougherty et al, 2018). Our observed exudation rates from root branches are in line with modeled or measured root exudation rates of diverse vegetation types (Finzi et al, 2015;Dror & Klein, 2021;Rog et al, 2021;Sell et al, 2021), although they are at the lower end of reported values from comparable temperate forests (Tückmantel et al, 2017;Meier et al, 2020) and other ecosystems (summary provided by Gougherty et al (2018). Discrepancies in exudate estimates across studies may arise as a result of methodological differences such as filter size variations (0.2 vs 0.7 µm) or the use of C-free materials (Gougherty et al, 2018), bedrock characteristics (Meier et al, 2020) or potential reuptake during longer collection periods (Oburger & Jones, 2018).…”
Section: Speciessupporting
confidence: 84%
“…In our study, the proportions of net-C assimilation allocated to root exudation were only 0.6 AE 0.1% and 1.8 AE 0.6% in control and drought plots, respectively, which were below the 3-30% previously reported at other study sites for multiple species (Kuzyakov & Domanski, 2000;Jones et al, 2009;Finzi et al, 2015;Abramoff & Finzi, 2016;Gougherty et al, 2018). Our observed exudation rates from root branches are in line with modeled or measured root exudation rates of diverse vegetation types (Finzi et al, 2015;Dror & Klein, 2021;Rog et al, 2021;Sell et al, 2021), although they are at the lower end of reported values from comparable temperate forests (Tückmantel et al, 2017;Meier et al, 2020) and other ecosystems (summary provided by Gougherty et al (2018). Discrepancies in exudate estimates across studies may arise as a result of methodological differences such as filter size variations (0.2 vs 0.7 µm) or the use of C-free materials (Gougherty et al, 2018), bedrock characteristics (Meier et al, 2020) or potential reuptake during longer collection periods (Oburger & Jones, 2018).…”
Section: Speciessupporting
confidence: 84%
“…Plants exhibit substantial variation in root exudation and root morphology in response to resource availability among and within species (Wen et al ., 2019; Meier et al ., 2020; Williams et al ., 2021), but our understanding of how root exudation (quantity and quality) covaries with root morphology remains inconclusive (Phillips et al ., 2008; Aoki et al ., 2012; Proctor & He, 2017; Wen et al ., 2019; Sun et al ., 2021). For example, across a range of species, the release of root exudates is either negatively (Lyu et al ., 2016; Wen et al ., 2019; Honvault et al ., 2021), positively (Aoki et al ., 2012; Guyonnet et al ., 2018; Akatsuki & Makita, 2020; Meier et al ., 2020; Wang et al ., 2021b), or not (Kidd et al ., 2015; Sell et al ., 2021; Sun et al ., 2021; Williams et al ., 2021) correlated with SRL or specific root surface area (SRA). Adjustments in both root morphology and root exudation are consider as major C expenses for plant roots (Lambers et al ., 2006).…”
Section: Relationships Between Root Exudation and Critical Root Funct...mentioning
confidence: 99%
“…Specifically, rapid root exudation is related to low RTD and, thus, associated with a fast strategy along the root conservation gradient (i.e. RTD–root [N] axis; Sell et al ., 2021; Sun et al ., 2021; Williams et al ., 2021); however, SRL is independent of RTD and the root conservation gradient (Wang et al ., 2018; McCormack & Iversen, 2019; Bergmann et al ., 2020; Han & Zhu, 2021). Thus, different groups of species (e.g.…”
Section: Relationships Between Root Exudation and Critical Root Funct...mentioning
confidence: 99%
See 1 more Smart Citation
“…Results in this study further confirm the role of small diameter young root segments in shaping root exudation. Sell et al 30 also indicated that greater mass-specific exudation flux was related to a higher proportion of pioneer roots, suggesting that an essential amount of C may be released by actively growing pioneer roots. According to Meier et al 9 , root systems with a high SRL have, on average, thinner roots, and the C costs of root construction and mycorrhizal symbiosis are reduced.…”
Section: Discussionmentioning
confidence: 99%